A profile of the engineering students’ conceptual understanding on electricity / Nazlinda Abdullah - Abdullah, Nazlinda (Institute of Graduate Studies, UiTM, 2014)
This study aimed in revalidating a reliable diagnostic instrument on electricity which emphasized on parallel resistors. At the same time, it has also established an academic profile of the engineering students’ conceptual understanding on electricity; examined the difficulty and discrimination level of the items and assessed the students’ conception and misconceptions on electricity. Five intact classes chosen by cluster sampling from fifteen existing classes of PHY193 were involved in this study, namely the second semester engineering students undergoing a Diploma in Engineering program. The respondents comprised 102 engineering students with 56 from the Electrical Engineering group, 28 from the Mechanical Engineering and 18 Civil Engineering students studying in a local university. The descriptive approach was used in this study, aimed at addressing the four research questions which examined the academic profiles of the engineering students’ conceptual understanding on electricity, analyzed the validity and reliability of the instrument PCCUT (Parallel Circuit Conceptual Understanding Test, PCCUT), assessed the items’ difficulty and discriminating levels and the students’ conceptions and misconceptions on electricity.